Analysis of reclaimed water application for irrigation using multi-criteria analysis - Albuquerque, António (2012)
Approximately 60% of the population of the Cova da Beira region (Portugal) lives in rural communities with less than 2,000 inhabitants and the wastewater treatment plants (WWTP) in the region are mainly septic tanks, constructed wetlands and trickling filters. The daily reclaimed water discharged into streams could be mainly reused for landscape irrigation of public parks and lawns and golf courses, which often means offsetting potable water for nonpotable purposes. However, those applications may require a polishing treatment to remove mainly pathogens, and trace elements. A one-year monitoring campaign was carried out in a biological aerated filter that treats the sewage of 4,000 inhabitants. The research included the measurement of the flow-rate and its characteristics in terms of pH, temperature, conductivity, BOD5, COD, TSS, TN, NH4, NO2, NO3, TP, Na, Mg, Ca, K, Cl, B, As, Cd, Cr, Cu, Hg, Ni, Pb, Zn, total coliforms (TC), faecal coliforms (FC), E. Coli and helminths eggs (HE). Results show that the effluent concentrations of BOD5, COD, TN, TP, K, Ca and phytotoxic elements (Na, B and Cl) are compatible with the international guidelines for irrigation reuse (crop irrigation). Values of conductivity are not a risk to soil salinity, but TC, FC and E. Coli values are not compatible with the reuse guidelines and, therefore, a final disinfection must be implemented to decrease the pathogenic content. The low nitrate concentrations (<5 mg L-1) are suitable for irrigation and constitute a very low risk for groundwater contamination. GIS-based multi-criteria analysis was performed combining reclaimed water characteristics, the type and needs of the dominant crop production and environmental, technical and economic criteria. The results showed that approximately 170,000 m3 of reclaimed water annually discharged in the local stream could be reused for irrigation of 30.53 ha fruits trees, corn, olive trees and vine, located at a distance of about 1.8 km from the WWTP. The use of reclaimed wastewater in rural areas brings other advantages such as the reduction of the residual pollution load discharged in water streams and the reduction of water abstraction volumes for irrigation, which are important environmental and economics benefits, especially in periods of water shortage.